6x+1=6x-1

Simple and best practice solution for 6x+1=6x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+1=6x-1 equation:


Simplifying
6x + 1 = 6x + -1

Reorder the terms:
1 + 6x = 6x + -1

Reorder the terms:
1 + 6x = -1 + 6x

Add '-6x' to each side of the equation.
1 + 6x + -6x = -1 + 6x + -6x

Combine like terms: 6x + -6x = 0
1 + 0 = -1 + 6x + -6x
1 = -1 + 6x + -6x

Combine like terms: 6x + -6x = 0
1 = -1 + 0
1 = -1

Solving
1 = -1

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| w2/3+w4/3=16/3 | | 4x^2+4-22=0 | | 1225+6x=1700 | | -20+19= | | 1/3z=5 | | 4/2x+20=22 | | 1225+6x=700 | | 5x-17=2x+13 | | 5x^2=12 | | -1=6y-11 | | 5/13x=25 | | 4x-7(3-3x)-9=x | | 7x+7=3x-5 | | 3m-6n=9n+12 | | -b+17= | | 3x-4y+8=26 | | 7+3t=(6-t)/2 | | a^2+3x=2a^2 | | -3(v-3)=3v-33 | | 12x=3y+6 | | -6a(-5)(2b)= | | 2x+3=57 | | 5(r-3)-2r=-30 | | Y-5=mx-2 | | 5t+3=-12 | | -10b+3(-1+b)= | | 8x-5/12=13/18 | | 8(7-p)-8=-16 | | 4x-18+8x=7x+3x+8 | | -3+n=6n+22 | | 3(x-2)=5x+4 | | 1/3x+15=20 |

Equations solver categories